(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
he research included four sections. The first section contained an introduction and the importance of the research. The researcher touched on the importance of testing and measurement in the sports field, especially the subject of selection. The focus was also on physical and motor tests. The importance of the research came through setting standard scores for some of the physical and motor abilities of young players in effective swimming. (200) m free. As for the problem of the research, it lies in the field tests being the basis that reveal the truth about the physical and motor level. As for the areas of research, they included the human field. Which represents a sample of (60) swimmers from the clubs of the governorates of the southern region for the sports season (2022-2023), and the temporal field is determined for the period from (9/1/2023) to (11/30/2023), while the spatial field was in swimming pools The clubs investigated in the southern region, and the researcher used the descriptive survey method, and the research sample consisted of (60) swimmers The research, and the researcher concluded in finding grades and standard levels in the tests of physical and motor abilities to select the (200) m freestyle young swimmers, so the researcher recommends that it is necessary to pay attention to the standardized tests and benefit from them in knowing the real level of the swimmers because it is one of the means of objective evaluation and because of its importance In identifying their levels in order to enhance their level of physical and motor performance.